In prayer and pains, through faith in Christ: The life and ministry of John Eliot - Curtis, Steve (Missiology, 2015)
While William Carey (1761–1834) is often hailed as the “Father of Modern Missions” for his innovative work in India and for advancing the modern theology of missions—particularly in his commitment to respect the indigenous culture—he nevertheless drew heavily on the work of those who had preceded him in the work of missions. Among his predecessors was the “Apostle to the (American) Indians,” John Eliot (1604–1690). For his part, Eliot was also the product of his predecessors, especially in his adoption of the then-popular notion of civility before conversion. However, Eliot was also an innovator to whom the world of missions owes a great debt. His commitment to learning the indigenous language (Algonquin), creating a written language and a grammar of it, and translating the Bible into it are worthy of special note, as is his commitment to training indigenous pastors and teachers. The ministry of Eliot informs the foundational tenets of contemporary missiology.